Method for hot press forming steel articles and steel articles

JP2023503360A5Active Publication Date: 2025-04-18TATA STEEL IJMUIDEN BV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022531073
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-11-27
Filing Date
2020-11-27
Publication Date
2025-04-18
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

Hot forming of uncoated steel blanks results in oxidation and surface cracking due to the low melting temperature and high reheating temperature of Zn and Zn-Fe compounds, leading to low in-service ductility and limited impact energy absorption in ultra-high-strength products.

Method used

A method involving continuous annealing and hot-dip galvanizing of steel strips with specific alloy compositions, including high Mn content, followed by reheating in a transformation interval temperature range to minimize grain boundary penetration and promote Mn partitioning into austenite, resulting in a microstructure with high retained austenite content.

Benefits of technology

The method achieves high strength, ductility, and bendability in hot-press formed steel products with minimized microcracking and improved corrosion resistance, enabling applications in automotive parts requiring high energy absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

1. A method of hot press forming an article from zinc or zinc alloy coated steel strip, the method comprising the steps of: The process of casting molten steel into slabs; reheating the slab, preferably at a temperature of at least 1150°C, preferably for at least 60 minutes; hot rolling the steel into strip at an exit finish hot rolling temperature FRT preferably above a temperature Ar3, where Ar3 denotes the temperature at which ferrite transformation begins in the steel during cooling; Coiling of hot rolled steel strip; Pickling of hot rolled steel strip; continuous annealing of the strip; hot dip galvanising a steel strip with zinc or a zinc alloy, The immersion time is 3 seconds or more. The bath temperature in the molten bath is maintained at 420℃ to 500℃. the zinc bath consists essentially of zinc and at least 0.1% Al, optionally up to 5% Al and optionally up to 4% Mg, the balance of the bath comprising additional elements and unavoidable impurities, each of the additional elements being independently less than 0.3% by weight; The process of hot pressing into an article The method is a product obtained by a method for producing steel, comprising:
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for hot press forming a steel article from a steel coated with zinc or a zinc alloy after continuous annealing, and to a molten zinc or zinc alloy coated steel article produced by hot press forming a zinc or zinc alloy coated steel.

Background Art

[0002] Hot press forming, also called hot stamping, hot forming, press stamping, and press hardening, is a technique for forming a steel blank and hardening it into a final formed article or final formed part.

[0003] Generally, a steel blank is reheated to an austenitizing temperature, usually 870 to 940 °C, soaked at that temperature, and then formed and press quenched in a press die. A high temperature is required to fully austenitize the steel and melt all the carbides. Press quenching results in a strong martensite structure in the steel substrate. Even when hot forming is carried out in the intercritical range to form a two-phase structure, the reheating temperature is 760 °C or higher.

[0004] It is known that hot forming of an uncoated steel blank causes oxidation. To reduce this effect, Zn- and Al-based coatings are applied. From the perspective of corrosion resistance, Zn-based coatings may also be preferred because they provide galvanic protection. However, due to the low melting temperature and high reheating temperature of Zn and Zn-Fe compounds, surface cracks may occur during hot forming, and the cracks are related to grain boundary penetration of zinc. One route explored to solve this problem is the modification of the Zn coating.

[0005] The ductility in use of current (ultra) high-strength hot-formed products is very low (less than 8%) due to the martensite or martensite-bainite microstructure obtained by press quenching. The martensite microstructure in hot-formed products is primarily intended to achieve the required strength level (over 1000 MPa). However, such a microstructure for hot-formed products can only yield a total elongation of about 6% at most. While a single-phase martensite microstructure can yield good bendability (e.g., over 100° at 1000 MPa, about 50° at 1500 MPa), the impact energy absorption capacity of these products is low due to the low total elongation. From US2016 / 0312323A1, a method for producing ultra-high-strength uncoated steel is known, among other things. This known method includes the steps of preparing an iron alloy containing carbon and more than 2.5 wt% manganese, annealing the iron alloy at a first temperature to form an annealing alloy, hot forming the annealing alloy at a second temperature to form an intercritical or austenite structure, and cooling the thus annealed austenite alloy to form ultra-high-strength steel. In one embodiment, the annealing alloy is subjected to hot forming in the intercritical annealing temperature range. In another embodiment, the hot forming temperature is in the austenitizing annealing range. The soaking time is approximately 1 to 10 minutes. In the examples, the thermal cycle of hot forming was simulated after a continuous annealing process of a cold-rolled sheet without inducing actual deformation. US2016 / 0312323A1 does not describe a method for continuous annealing or a method for applying coatings to steel strips. EP18155866 describes a method for hot forming a steel blank coated with Zn or a Zn alloy containing more than 3.1% by weight of Mn, employing a soaking time of no more than 3 minutes. EP18155866 does not describe a method for coating a steel strip with Zn or a Zn alloy, nor does it consider a soaking time of more than 3 minutes during reheating.For effective diffusion to occur, a longer soaking time is preferable for steels containing a relatively large amount of Mn. [Overview of the Initiative]

[0006] The object of the present invention is to provide cathodic protection for hot-pressed steel strip articles provided by zinc-based coatings on (ultra) high-strength steel, while reducing the risk of (micro) crack formation.

[0007] Another object of the present invention is to provide a hot-dip galvanizing process that enables the coating of steel strips containing a large amount of Mn with Zn or a Zn alloy, while simultaneously providing a continuous annealing process that results in a desired microstructure for achieving high ductility in the final product.

[0008] Another object of the present invention is to provide hot-pressed molten zinc or zinc alloy coated steel articles that have high strength and high deformability at room temperature. [Brief explanation of the drawing]

[0009] [Figure 1] Figure 1 is a schematic diagram showing the continuous annealing-hot galvanizing cycle and the subsequent hot forming cycle. [Figure 2] Figure 2 shows an extracted sample for microcrack inspection after hot forming ((a) actual Ω-shaped profile (Ω-shaped profile) (b) approximate location). [Modes for carrying out the invention]

[0010] Therefore, the method according to the present invention is a method for hot-press forming a steel article from a zinc or zinc alloy coated steel strip, The steel strip has the following composition by weight: C:0.05~0.3; Mn: 3.0~12.0; Al:0.04~3.0; Depending on the case, the following additional alloying elements may be used: Si: Less than 1.5 Cr: Less than 2.0 V: Less than 0.1 Nb: Less than 0.1 Ti: Less than 0.1 Mo: Less than 0.5 One or more of the following; Inevitable impurities (e.g., S: less than 30 ppm by weight, P: less than 0.04); and Fe: remainder It has, A method for manufacturing zinc or zinc alloy coated steel strips involves the following steps: The process of casting molten steel into a slab; A process of reheating the slab to a temperature exceeding 1150°C and holding it at that temperature for 60 minutes or more; The process involves hot-rolling steel into strips, preferably at an exit finish hot-rolling temperature FRT above a temperature Ar3, where Ar3 is the temperature at which ferrite transformation begins in the steel during cooling; The process of winding up hot-rolled steel strips; The process of pickling hot-rolled steel strips; In some cases, the process involves cold-rolling the pickled hot-rolled steel strip into a cold-rolled steel strip, where, In the case of cold rolling, the hot-rolled strips, after being wound and pickled, are subjected to batch annealing at a temperature TB for a time PB. The temperature TB and time PB are selected such that the microstructure of the steel after cooling to room temperature exhibits more than 60 volume% ferrite, and in a preferred embodiment, the temperature TB is selected to be 650°C or less and the time PB is 24 hours or more; A process of continuously annealing a strip according to an annealing thermal cycle, where, The temperature of the steel strip rises in the heating section, preferably at a rate of 1-15°C / second in the heating section, and then remains at a relatively stable level for soaking in the soaking section. The soaking atmosphere is maintained at a temperature of TMIN~TMAX. TMIN is (TMAX - 100°C), Continuous annealing is considered to end when the temperature of the steel strip is decreased in the annealing heat cycle, preferably when it is decreased at a rate of from 0.5 to 10°C / second. TMAX is not higher than the lowest temperature of (Ac3 - 100°C) and 700°C. The dew point of the soaking atmosphere is from -40°C to -10°C. Continuous annealing includes pre-oxidizing the steel strip in an annealing atmosphere having an oxygen content of 500 to 3000 volume ppm in the heating section. The soaking atmosphere is a reducing atmosphere, preferably a reducing atmosphere containing from 1 to 15 volume % of hydrogen in nitrogen. The time of continuous annealing consisting of the time of the heating section and the time of the soaking section is 150 seconds or longer, preferably 180 seconds or longer. A step of hot-dip galvanizing the steel strip with zinc or a zinc alloy, where the dipping time is 3 seconds or longer. in the molten bath, the bath temperature is maintained at 420°C to 500°C. The zinc bath essentially contains zinc and contains at least 0.1 wt% of Al, optionally up to 5 wt% of Al and optionally up to 4 wt% of Mg. The remainder of the bath contains additional elements and unavoidable impurities, and the additional elements are each independently less than 0.3 wt%. including A method of hot press forming a steel article includes the following steps: A step of preparing a blank cut out from a hot-dip galvanized steel strip with zinc or a zinc alloy; A step of reheating the blank to a blank temperature TRH of (Ac3 - 300°C) to 750°C; A step of soaking the blank at TRH for a period of longer than 3 minutes and up to 15 minutes; A step of transferring the blank to the press within 30 seconds; A step of forming a steel article in a press and then cooling the steel article; A step of removing the steel article from the press which is a method including these steps.

[0011] Using a specific manufacturing process, steel having a specified composition is processed into a hot-rolled strip or a cold-rolled strip. Then, using the processing temperature and time of this method, and the dew point and atmosphere in different sections, the steel is continuously annealed, as a result, surface enrichment of alloy elements of the steel is prevented, thereby providing a surface suitable for good adhesion of a Zn or Zn alloy coating by hot-dip galvanizing to the steel substrate. The specified continuous annealing process is carried out at a low intercritical temperature which is below the lowest of (Ac3 - 100°C) or 700°C, as a result, Mn distribution occurs between the ferrite phase and the austenite phase of the steel, thereby enabling the formation of a desired microstructure containing a large amount of retained austenite after hot press forming. Then, the Zn or Zn alloy-coated steel strip in blank form is reheated at the same intercritical temperature range ((Ac3 - 300°C) to 750°C, preferably (Ac3 - 300°C) to 700°C) for 3 minutes or more, thereby Mn distribution can occur again between ferrite and austenite. The reheating temperature of the blank is selected so that grain boundary penetration of liquid Zn or Zn alloy does not occur, minimizing surface microcracks of the steel article during hot forming. Preferably, in a hot press formed hot-dip galvanized or zinc alloy-coated steel composed of a steel substrate provided with a hot-dip galvanized coating layer, the length of microcracks of the steel substrate is 5 μm or less.

[0012] In the case of steel containing 3 to 12% by weight of Mn (conventionally called "medium Mn steel"), a Zn or Zn alloy coating having good adhesion can be applied to the strip surface by hot-dip galvanizing.

[0013] Immediately before immersing the steel in a high-temperature bath of Zn or a Zn alloy, the steel is subjected to continuous annealing at the transformation interval temperature, enabling effective Mn distribution between the ferrite and austenite phases of the steel. This feature assists Mn distribution during subsequent reheating of Zn or Zn alloy coated steel for hot-press forming, providing the desired final microstructure with a large amount of retained austenite.

[0014] By reheating the Zn or Zn alloy coated steel blank at a temperature of (Ac3-300°C) to 750°C, preferably (Ac3-300°C) to 700°C, the formation of liquid Zn or Zn alloy and their penetration into the grain boundaries of the steel substrate are minimized during a reheating time of 3 minutes or more.

[0015] The above reheating, selected from the transformation interval temperature range of the steel, also ensures that further Mn distribution occurs between ferrite and austenite, which occurred during the preceding continuous annealing. Reheating times of 3 minutes or more cause a more effective distribution of Mn, resulting in higher thermal stability of the austenite phase and a higher percentage of retained austenite after the article cools to room temperature.

[0016] In one embodiment of this method, the Mn content of the steel is 6.0% by weight or more. This significantly reduces the Ac3 temperature of the steel, as will be described later. As a result, the formation of a Zn-rich liquid phase that occurs during the reheating of the blank and hot press forming is suppressed. This suppresses zinc-induced liquid metal embrittlement and minimizes microcracks in the hot-formed article. Furthermore, this preferred embodiment, by enabling a reduction in the required reheating temperature, also saves energy costs in hot press forming and reduces oxidation of the zinc coating on the steel surface. This improves the weldability of the hot-formed article and eliminates the need to sandblast the article after hot forming.

[0017] In one embodiment of this method, the slab is reheated to a temperature exceeding 1200°C, preferably exceeding 1250°C, and held at this temperature for 60 minutes or more. This provides the effect of uniformly distributing Mn within the as-cast steel slab.

[0018] In a further embodiment of this method, the slab is reheated to a certain temperature and held at this temperature for 120 minutes or more. This results in a more uniform distribution of Mn within the as-cast steel slab, minimizing microsegregation.

[0019] In another embodiment of this method, TRH is (Ac3-300℃) to 700℃. This minimizes the amount of zinc-rich liquid phase formed on the steel surface, reducing the possibility of the liquid phase penetrating the steel substrate. As a result, it further minimizes or eliminates zinc-induced liquid metal embrittlement and microcrack phenomena.

[0020] In yet another embodiment of this method, the blank is transferred to the press within 10 to 15 seconds. This minimizes temperature loss of the steel blank, making it easier to form the article and minimizing or eliminating springback of the formed article.

[0021] The present invention also relates to a hot-pressed molten zinc or zinc alloy coated steel article that can be obtained by the method described in any one of claims 1 to 5, in volume % Ferrite: 30% or more, preferably 40% or more; Residual austenite: 20% or more, preferably 30% or more; Martensite: 40% or less (including 0%), preferably 30% or less (including 0%) This is embodied in hot-pressed molten zinc or zinc alloy coated steel articles, including the following:

[0022] Such a microstructure of a steel article containing 20% ​​or more by volume, preferably 30% or more by volume, of retained austenite in combination with a predetermined amount of ferrite and martensite, achieves high levels of ductility, expressed as total elongation and bendability. These microstructures also ensure that high strength values ​​are achieved in the article, which is due in particular to the retained austenite that transforms into strong martensite during cold deformation, e.g., impact, and the martensite that is initially present in the article's microstructure.

[0023] In one embodiment of the present invention, a hot-pressed molten zinc or zinc alloy coated steel product has the following mechanical properties: a yield strength of 800 MPa or more, a maximum tensile strength of 820 MPa or more, a total elongation of 10% or more, and a bending angle of 80° or more at a thickness of 1 mm. Such articles are particularly suitable for automotive applications, such as front or rear axial bars, lower B-pillars, bumper beams, etc. Due to the high mechanical properties (i.e., total elongation, bendability, and strength values), high impact energy absorption can be achieved in the article.

[0024] The present invention is based on modifications to the composition of a steel substrate provided with a zinc or zinc alloy-based coating, the design of a process route that allows the steel to be manufactured in a cold-rolled and / or hot-rolled form, the design of a continuous annealing and hot-dip galvanizing process that makes the steel suitable for coating with Zn or a Zn alloy and causes a favorable microstructural change in the steel substrate for subsequent hot stamping, and the design of a hot stamping process.

[0025] The essential elements for modifying steel substrates are Mn, C, and Al. Increasing the Mn content in steel lowers the austenite transformation temperature (both the temperature at which austenite transformation begins (Ac1) and the temperature at which it is completed (Ac3) during heating). This allows for annealing of steel at lower temperatures in the transformation interval phase region.

[0026] This suppression of the austenite transformation temperature has the following advantages:

[0027] • A low soaking temperature reduces the diffusion of alloying elements and the subsequent selective oxidation of the outer alloying elements. It is necessary to note that the high Mn content of the steel substrate increases the likelihood of selective oxidation of the outer Mn, hindering wettability by liquid zinc.

[0028] Reheating of Zn or Zn alloy coated steel blanks can also be done at relatively low temperatures, which minimizes the growth of thick oxides and thus preserves more metallic zinc.

[0029] The hot-press molding temperature is also reduced. This minimizes the formation of liquid zinc and its penetration into grain boundaries, significantly reducing microcracks caused by zinc.

[0030] The steel substrate is annealed and reheated within the transformation zone temperature range to achieve the desired microstructural composition, ensuring high mechanical properties. This metallurgical requirement also contributes to the present invention. When steel is annealed and / or reheated and hot-formed at temperatures above Ac3, i.e., at the austenite temperature, the desired microstructure cannot be achieved. When these heat treatments are performed at temperatures above the Ac3 of the steel, a single phase of austenite exists at the soaking temperature, and the composition of this austenite is assumed to be the bulk composition of the steel with low thermal stability. On the other hand, when soaking is performed at the transformation zone annealing temperature, two phases, austenite and ferrite, coexist at the soaking temperature. This allows for the distribution of alloying elements between austenite and ferrite. The steel of the present invention contains Mn, C, and Al as essential alloying elements. Therefore, Mn and C are γ-forming elements and are therefore distributed more in austenite, while Al is an α-forming element and is therefore distributed more in ferrite. The low heat treatment temperature also ensures that the grain size of the steel remains fine. Low-temperature transformation zone heat treatment yields an ultrafine microstructure (crystal grain size of 2 μm or less) that improves the strength and ductility of the product.

[0031] Herein lies another important aspect of steel modification. Due to the high Mn content (3-12 wt%) in the steel, the distribution process during annealing and reheating in the transformation zone temperature range leads to high Mn enrichment in the austenite. This Mn enrichment, along with carbon enrichment, enhances the thermal stability of the transformation zone austenite. Therefore, during cooling to room temperature or rapid cooling, the transformation zone austenite does not transform much into martensite or any other phase, and as a result, a large amount of austenite (more than 20 vol%) can be retained in the steel's microstructure. During loading, the retained austenite transforms into martensite, causing a transformation-induced plasticity (TRIP) effect. The TRIP effect, which increases the work hardening rate or strain hardening rate, allows for high strength, high elongation, and high bendability in the product. A manganese content exceeding 12% by weight makes continuous casting of steel difficult due to extreme segregation and changes the mechanism of plasticity enhancement from TRIP to TWIP (twin-induced plasticity). A content of less than 3% by weight does not result in sufficient manganese enrichment in austenite and does not achieve a sufficient amount of retained austenite at room temperature.

[0032] Similar to the effect of Mn described above, C also enriches the austenite transformation zone, increasing the thermal stability of the austenite and causing austenite stabilization in the microstructure at room temperature. However, C is effective in smaller amounts than Mn, and therefore the range of C content for modifying the steel chemistry in this invention is 0.05 to 0.3 wt%. If the C content is less than 0.05 wt%, a sufficient austenite stabilization effect is not obtained, and if the C content exceeds 0.3 wt%, post-processing of the manufactured article, such as spot welding, becomes difficult. Welding is an essential process when assembling automotive parts to the vehicle body, and therefore welding is a very important aspect to consider. C is also added to the steel of this invention to increase its strength.

[0033] Aluminum is a ferrite-stabilizing element of steel, not an austenite-stabilizing element. However, it is added to steel in amounts of 0.04–3 wt% to extend the transformation interval temperature range (Ac1–Ac3) of the steel. High levels of Mn make the steel sensitive to slight variations in processing temperature, resulting in altered microstructure and variable mechanical properties. The addition of Al ensures the robustness of the steel's processing, allowing for the selection of annealing and reheating temperatures with slight variations to achieve the desired mechanical properties. Except for the minimum level required for deoxidation of the steel (i.e., less than 0.04 wt%), the present invention still works, although a more precise furnace is required if Al is not present in the steel. To suppress the formation of oxide scales during hot rolling and reduce rolling loads during hot and cold rolling, the maximum amount of Al is limited to 3 wt%.

[0034] Since steel contains a relatively large amount of alloying elements, particularly manganese (Mn), for processing steel into hot and / or cold-rolled strips, the present invention requires the use of a unique processing step. Mn tends to segregate after casting if its content exceeds about 2% by weight. This can interfere with the performance of the product by resulting in non-uniform properties and can also cause cracking. Therefore, it is necessary for the cast slab to be sufficiently homogenized. This is achieved by exposing the slab to a relatively high temperature, above 1150°C, preferably above 1200°C, for a sufficiently long time, preferably 60 minutes or more.

[0035] Next, due to the high alloy content, the rolling load during hot rolling of the strip is high. Hot rolling of steel is made possible by using relatively high-temperature hot rolling in the austenite temperature range. The finish rolling temperature (FRT) is kept well above temperature Ar3 (it can be above 900°C) in order to keep the required hot rolling load relatively low.

[0036] Furthermore, if cold rolling is optionally applied to hot-rolled strips to reduce the gauge of the final steel product, the material cannot be cold-rolled unless appropriate pretreatment is employed. In particular, hot-rolled steel in a coiled state (as-coiled) is subjected to batch annealing, preferably at a low temperature within the steel's transformation interval temperature range for 24 hours or more. This batch annealing temperature should preferably be below 650°C, because at higher temperatures, a large amount of retained austenite is formed after the steel cools to room temperature. Also, using high batch annealing temperatures can result in a large amount of martensite appearing in the microstructure. Both martensite and retained austenite make cold rolling difficult by increasing the rolling load. The martensite phase is hard, but retained austenite transforms into hard martensite during cold rolling, which itself increases the rolling load. Therefore, batch annealing of the wound material is desirable to maintain lower levels of retained austenite and martensite content and increase the amount of ferrite. The ferrite phase does not work harden as much as retained austenite during cold rolling, thus allowing for lower rolling loads and enabling cold rolling.

[0037] Next, in the treatment of steel, the present invention requires the design of a continuous annealing process in such a manner that the steel surface remains clean and oxide-free during continuous annealing, suitable for the subsequent hot-dip galvanizing process. The continuous annealing and hot-dip galvanizing process of the present invention is schematically shown on the left side of Figure 1. The challenge is that the continuous annealing process must, in addition to producing a steel surface suitable for good adhesion of Zn or Zn alloy, also provide a microstructure of the steel substrate in which sufficient distribution of Mn and C between ferrite and austenite occurs, resulting in a high proportion of retained austenite in the substrate before reheating in hot-press forming. To achieve both requirements, the maximum soaking temperature TMAX during continuous annealing is kept below the lowest of (Ac3-100°C) and 700°C. This temperature lies within the transformation interval temperature range of the steel, optimized to obtain the maximum Mn distribution to austenite. Regardless of the chemical composition of the steel of the present invention, temperatures above 700°C result in severe selective oxidation of the outer surface of the steel. Sufficient Mn distribution from ferrite to austenite is ensured by a soaking time of at least 150 seconds, preferably 180 seconds or more. Since Mn is a relatively large substitutional alloying element in steel and diffuses slowly, shorter soaking times do not result in sufficient Mn enrichment in austenite and thus insufficient thermal stability. On the other hand, carbon is a small interstitial alloying element in steel and can diffuse faster than Mn. Therefore, the minimum soaking time requirement is primarily determined by the diffusivity of Mn rather than C. A heating rate of 1-15°C / second to the soaking temperature is preferable. A slow heating rate makes continuous annealing operation uneconomical, while a fast rate makes continuous annealing line operation extremely dangerous and therefore impractical.

[0038] Apart from maintaining the low soaking temperature mentioned above during continuous annealing, the annealing atmosphere also needs to be controlled in order to adapt the surface of the steel substrate to good adhesion of Zn or Zn alloy in hot-dip galvanizing. Therefore, the annealing atmosphere during heating of the steel strip to the soaking temperature is maintained in an oxidizing state, typically with an oxygen content of 500-3000 ppm by weight. This pre-oxidizing atmosphere causes selective oxidation of the interior, forming a thin layer of wustite. Then, during soaking of the steel substrate at the annealing temperature, a reducing atmosphere, preferably a reducing atmosphere containing 1-15 volume% hydrogen in the annealing atmosphere, is maintained. The reducing atmosphere during soaking reduces the wustite. At the soaking temperature of this application, the enrichment of alloying elements is slowed due to the slow diffusion rate of alloying elements. An oxygen content of less than 500 ppm by weight during heating causes oxidation of Mn and Si atoms on the surface of the steel, ultimately resulting in poor wetting of the liquid zinc. In contrast, oxygen content exceeding 3000 ppm by weight causes excessive oxidation of Fe, resulting in the formation of a thick FeO layer on the steel surface. This surface is unsuitable for adhesion of Zn or Zn alloys. Furthermore, these FeO particles can be picked up by the rolls during the manufacturing process, leading to numerous surface defects.

[0039] After confirming that the steel substrate surface is not enriched with alloying elements as described above during continuous annealing, the steel strip is immersed in a bath containing liquid Zn or Zn alloy maintained at a temperature of 420°C to 500°C. At bath temperatures below 420°C, Zn remains in a solid state, while at bath temperatures above 500°C, excessive vaporization of the liquid Zn or Zn alloy occurs. The typical temperature optimized for the viscosity of the liquid and its vaporization is 450 to 465°C. Furthermore, the immersion time of the steel strip in the liquid bath of Zn or Zn alloy is also important. The time is determined by the speed at which the steel strip passes through the continuous annealing line. The line speed of the continuous annealing equipment needs to be adjusted so that the immersion of the steel strip in the zinc plating bath is ensured for at least 3 seconds. A time of 3 seconds or more is necessary to obtain good adhesion between the steel strip and the Zn or Zn alloy.

[0040] The above hot-dip galvanizing conditions are applicable to a zinc bath that essentially contains zinc, at least 0.1% by weight of Al, optionally up to 5% by weight of Al, and up to 4% by weight of Mg, with the remainder of the bath containing additional elements and unavoidable impurities, each of which is independently less than 0.3% by weight. Therefore, the present invention is not limited to pure Zn coatings but is applicable to a wide range of Zn-based coating variations.

[0041] The present invention relating to the hot-press forming of steel substrates and the processing thereof into coated strips works in conjunction with a hot forming process, which is also part of the present invention. The hot forming cycle is schematically shown on the right side of Figure 1. According to the present invention relating to the hot pressing of Zn or Zn alloy coated steel strips or blanks, it is necessary to reheat at a low temperature within a specially specified transformation interval temperature range of the steel substrate. A typical reheating temperature TRH is (Ac3-300°C) to 750°C, preferably (Ac3-300°C) to 700°C. The selection of this temperature range is based on several considerations, as follows:

[0042] • Complete austenitization is not necessary.

[0043] The hot-formed parts of the present invention do not require sandblasting to remove zinc oxide before welding, as is done with conventional hot-formed steel, because the zinc oxide present after heat treatment is still very thin. This reduces the manufacturing cost of hot-formed parts by reducing sandblasting costs and improving spot weldability.

[0044] The essential characteristics of the microstructure of the steel substrate of this invention do not change significantly during the hot press forming process. Therefore, the pressing temperature can be lower than in conventional hot press forming. In this way, metal embrittlement due to zinc can be minimized. By minimizing the occurrence of microcracks during hot forming, high fatigue resistance and durability are achieved.

[0045] The low-temperature reheating described above also minimizes oxidation of the Zn or Zn alloy coating, allowing the metal coating to maintain a relatively thick state. As a result, good cathodic protection is provided to the steel substrate, improving the corrosion resistance of the product.

[0046] The above advantages of selecting a low reheating temperature in hot forming relate to the Zn or Zn alloy coating on the steel substrate. This selection of the blank's reheating temperature also contributes to the development of a proper microstructure in the steel substrate, achieving the desired mechanical properties and ultimately mechanical performance. As described above, the substrate during the preceding continuous annealing process already forms a considerable amount of retained austenite due to the selection of a soaking temperature within the transformation zone temperature range of the steel substrate. Reheating in the transformation zone for hot forming adds to this by further promoting the distribution of Mn and C into the austenite, resulting in retained austenite with higher mechanical stability being obtained in the hot-formed steel substrate. The reheating process also generates an additional amount of retained austenite due to the additional opportunity for austenite-stabilizing elements to diffuse into the transformation zone austenite.

[0047] The reheated blank is then transferred to a forming tool, typically a press, where it is deformed into the desired shape. To avoid excessive cooling of the blank, the transfer time is preferably within 30 seconds, more preferably within 10-15 seconds. After forming with the press, the article is cooled. Press quenching, which is essential in conventional hot forming, is not necessary in this invention. This is because the transformation section austenite, which has a large amount of Mn, is very stable, and when it partially transforms into martensite, it becomes very hardenable, thus eliminating the need for high-speed press quenching. The formed article may be removed from the press and cooled in the ambient atmosphere. Forced cooling with air, or a combination of (forced) cooling in air followed by press quenching, is also possible.

[0048] The reheated blank is transferred from the furnace or other heating device to a forming tool for deformation. As described above, the transfer time is preferably short, preferably within 10 to 15 seconds. In an advantageous embodiment, the temperature drop of the steel blank during transfer does not exceed 150°C. Preferably, the temperature drop is 100 to 150°C. If the temperature drop is large, the blank may become excessively rigid and may not deform in the subsequent forming process.

[0049] Furthermore, since press hardening is not strictly required, the present invention makes it possible to remove the formed article from the hot forming press immediately after forming, for example, at an exit temperature of 100-450°C, for example, 200-425°C.

[0050] In one embodiment, this cooling process is carried out inside the press, preferably to a temperature of 100-250°C, more preferably 150-200°C. From the viewpoint of the hardening properties of the modified steel substrate, a cooling rate of at least 3°C / second is appropriate. Even this relatively slow cooling rate ensures that austenite is transformed back into martensite in the formed article. Advantageously, the quenching rate is at least 5°C / second. After being removed from the press, the formed article is further cooled to ambient temperature.

[0051] The key to achieving the mechanical properties in this invention lies in the above-described process chain of the modified steel substrate's chemical composition, which results in a unique microstructure in the final hot-formed state. The chemical composition of the steel modified by the present invention yields at least 20 vol% retained austenite and at least 30 vol% ferrite, while martensite is 40 vol% or less (including 0 vol%). This relatively high proportion of retained austenite is metastable, resulting in a TRIP effect that achieves a combination of high strength, elongation, and bendability, leading to high impact resistance in hot-formed molten zinc or zinc alloy coated steel articles. Even when retained austenite is relatively stable, its intrinsic ductility is higher than that of ferrite and martensite due to its face-centered cubic (FCC) crystal structure, resulting in high ductility values.

[0052] The steel used in the method of the present invention is a conceptual steel containing carbon, manganese, and aluminum as its main components. Optionally, other alloying elements selected from silicon, chromium, vanadium, niobium, titanium, and molybdenum may be present. Inevitable impurities, such as N, P, S, O, Cu, Ni, Sn, Sb, etc. (derived from the starting materials for preparing the steel having this composition), may be present but in very low concentrations. These are not intentionally added and are not specifically controlled within predetermined limits. The remainder of the steel having this composition is iron.

[0053] Carbon is present in an amount of 0.05 to 0.3 wt%, preferably 0.05 to 0.25 wt%, and more preferably 0.08 to 0.2 wt%. While carbon is added primarily for strength, it also contributes to austenite stabilization. In this composition, the austenite-stabilizing effect of manganese is far more pronounced due to its high proportion. If the amount of carbon is too low, the desired strength level of 820 MPa or higher, preferably 1000 MPa or higher, cannot be obtained, and if the amount of carbon exceeds 0.3 wt%, the weldability of the molded part may decrease.

[0054] Manganese is present in a concentration of 3.0–12.0 wt%. Manganese induces the TRIP effect by lowering the temperatures Ac1 and Ac3, stabilizing austenite, increasing strength and toughness, and stabilizing austenite in the microstructure at room temperature. Below 3.0 wt%, the desired effect is not achieved, while above 12.0 wt%, casting and segregation problems arise. The deformation mechanism also changes from transformation-induced plasticity (TRIP) to twinning-induced plasticity (TWIP). If the Mn content is too low, sufficient austenite is not retained at room temperature, the stability of retained austenite becomes too low, and as a result, the ductility benefit cannot be obtained. Preferably, the Mn content is 3.5–10.5 wt%. In one embodiment, the Mn reaches 5.0–9.0 wt%. In other embodiments, it is 5.5–8.5 wt%, for example, 6.0–7.5 wt%.

[0055] Aluminum may be added to extend the temperature range of Ac1 to Ac3 and improve the robustness of the process from an industrial standpoint. Al is present in an amount of 0.04 to 3.0% by weight, preferably 0.5 to 2.5% by weight, and more preferably 1.0 to 2.2% by weight.

[0056] If silicon is present, it is added in amounts of less than 1.5% by weight to enhance strength through solid solution strengthening. If present, the amount is typically between 0.01% and 1.5% by weight. The preferred range is 0.1 to 1.0% by weight.

[0057] Both Al and Si suppress cementite precipitation, thus avoiding a decrease in ductility. Furthermore, both Al and Si increase the peak annealing temperature to obtain the maximum amount of retained austenite at room temperature. Therefore, during the transformation interval annealing, Mn diffusion is promoted, resulting in effective Mn distribution in the austenite.

[0058] Optionally, one or more additional microalloying elements selected from group V, Nb, Ti, and Mo are present. These microalloying elements enhance strength through precipitation hardening by carbides, nitrides, or carbonitrides. Another optional element of the present invention, Cr, also increases the peak annealing temperature to achieve the maximum amount of retained austenite at room temperature and reduces the sensitivity of retained austenite content to the annealing temperature. These result in effective Mn distribution in the austenite and improved robustness of the process during annealing. If present, preferred additions of these optional alloying elements are V: 0.01-0.1 wt%; and / or Nb: 0.01-0.1 wt%; and / or Ti: 0.01-0.1 wt%; and / or Mo: 0.05-0.5 wt%; and / or Cr: 0.1-2.0 wt%.

[0059] The composition of the zinc or zinc alloy coating is not limited. Hot-dip galvanizing can be carried out using a standard GI coating bath, where GI stands for "ordinary galvanizing, i.e., hot-dip galvanizing using a bath mainly containing zinc." Several zinc coating baths can be applied, for example, a zinc bath that essentially contains zinc, along with at least 0.1 wt% Al, optionally up to 5 wt% Al, optionally up to 4 wt% Mg, with the remainder of the bath containing additional elements, each independently less than 0.3 wt%, and unavoidable impurities. A zinc alloy coating layer can be realized containing 0.3 to 4.0 wt% Mg and 0.05 to 6.0 wt% Al and optionally up to 0.2 wt% of one or more additional elements along with unavoidable impurities, with the remainder being zinc. For example, to form spangles and / or to prevent dross formation, additional elements may be present in small amounts of less than 0.3 wt%. Other additional elements may be selected from the group including Pb, Sb, Ti, Ca, Mn, Sn, La, Ce, Cr, Ni, Zr, and Bi. Small amounts of such additional elements will not significantly alter the properties of the bath or the resulting coating in typical applications. Preferably, if one or more additional elements are present in the coating, each is present in less than 0.02% by weight, and preferably each is present in less than 0.01% by weight.

[0060] The resulting hot-pressed molten zinc or zinc alloy coated steel article is preferably, by volume %, Ferrite: 30% or more, preferably 40% or more; Residual austenite: 20% or more, preferably 30% or more; Martensite: 40% or less (including 0%), preferably 30% or less (including 0%) It has a three-phase or two-phase microstructure, including [specific components].

[0061] Advantageously, the resulting molded article has the following characteristics: Yield strength: 800 MPa or higher, preferably 850 MPa or higher, more preferably 900 MPa or higher; Tensile strength: 820 MPa or higher, preferably 1000 MPa or higher; Total elongation: 10% or more, preferably 15% or more, more preferably 25% or more; Minimum bending angle at a thickness of 1.0 mm: 80° or more, more preferably 90° or more. It has.

[0062] The proportions of the phases described above were determined using X-ray diffraction (XRD). The amount of retained austenite was determined by XRD at a position where the sample thickness was 1 / 4. The XRD patterns were recorded in the range of 45–165° (2θ) using a Panalytical Xpert PRO standard powder diffractometer (CoKα). Quantitative determination of the phase ratio was performed by Rietveld analysis using the Bruker Topas software package for Rietveld refinement. Martensite content was determined from peak splitting at the ferrite diffraction position in the diffraction pattern. The grain size of the phases can be determined from scanning electron microscope images of the microstructure.

[0063] Yield strength, maximum tensile strength, and total elongation are measured quasi-statically at room temperature (strain rate 3 × 10⁻¹⁰) in accordance with NEN10002 standard. -4 s -1 The properties were determined from tensile tests. The tensile test specimens had a gauge length of 50 mm, a width of 20 mm, and a nominal thickness of 1.5 mm in the rolling direction. The flexibility was determined by a three-point bending test in accordance with the VDA238-100 standard on a 40 mm × 30 mm specimen with a nominal thickness of 1.5 mm, in both the longitudinal and transverse directions. The bending axis was along the 30 mm dimension, and the bending radius was 0.4 mm. The bending angles obtained from the nominal 1.5 mm specimens were converted to angles corresponding to a thickness of 1.0 mm using the following formula: Bending angle at a thickness of 1.0 mm = Measured angle × Square root of the actual thickness (mm). From these converted bending angles, the minimum values ​​for the longitudinal and transverse specimens for specific heat treatment conditions were adopted to claim the scope of the present invention.

[0064] As described above, by using a continuous annealing process at the transformation zone temperature in the manufacture of steel strips before reheating the blanks cut from the strips, Mn distribution from ferrite to austenite occurs, making the transformation zone austenite even more stable. During cooling after transformation zone annealing and hot-dip galvanizing, the transformation zone austenite does not transform much into martensite due to its high stability and low Ms (i.e., high thermal stability), resulting in a three-phase (ferrite + retained austenite + martensite) or two-phase (ferrite + retained austenite) microstructure. In the case of high Mn content (e.g., more than 10.5 wt%), a complete two-phase structure can be obtained, and in the case of Mn content less than 10.5 wt%, a three-phase structure is formed. Furthermore, by increasing the Mn level, a lower reheating temperature T RH (For example, below 700°C) and a large amount of retained austenite (20% by volume or more) can be guaranteed. This large amount of retained austenite completely or partially transforms into martensite during deformation, causing a transformation-induced plasticity (TRIP) effect and resulting in a high strain hardening rate (= high elongation and high strength).

[0065] When steel strips are annealed in the transformation zone at temperatures below 700°C (using a continuous annealing process), a large amount of retained austenite is present, resulting in strips with high strength and ductility. Reheating for hot forming in the transformation zone temperature range (below 750°C or preferably below 700°C) also results in additional Mn distribution, improving austenite stability. However, if the annealing and reheating temperatures differ, some redistribution of Mn may occur. This may, in some cases, result in slightly less retained austenite after hot forming than after continuous annealing and hot-dip galvanizing. Nevertheless, a large amount of retained austenite (20% by volume or more) is still obtained for the present invention to function. If martensite is present, it may be slightly tempered, but this phenomenon contributes to even higher elongation.

[0066] Due to the steel composition and the annealing and reheating processes of the strips and blanks used, the residual elongation (or ductility in use) of the article is preferably 25% or more. It is preferable to use the transformation zone annealing and transformation zone reheating processes of the medium-Mn steel approach to obtain a mixed microstructure of ultrafine ferrite (0.5-2.0 μm), martensite, and high-residual austenite regions. As a result, high ductility is obtained in the final product.

[0067] Preferred hot-pressed molten zinc or zinc alloy coated steel articles are automotive parts, such as front or rear axial bars or bumper beams, particularly those requiring high energy absorption combined with high strength. Non-limiting examples include B-pillars and structural parts of the chassis. [Examples]

[0068] The present invention will be described with reference to the following embodiments. Refer to the following drawings.

[0069] Figure 1 shows a schematic diagram of the continuous annealing-hot galvanizing cycle and the subsequent hot forming cycle.

[0070] Figure 2 shows an extracted sample for microcrack inspection after hot forming ((a) actual Ω-shaped profile (b) approximate location).

[0071] Three steel ingots A, B, and C, having the chemical composition of the present invention and measuring 200 mm × 100 mm × 100 mm, were cast by melting the charge in a vacuum induction furnace. The chemical compositions of these steels are shown in Table 1, along with those of the conventional 22MnB5 steel commonly used for hot forming. The 22MnB5 steel was received with a GI coating to a thickness of 1.5 mm and further processed for comparison. The ingots of steels A, B, and C of the present invention were reheated at 1250°C for 2 hours and roughly rolled to a thickness of 25 mm. The strips were then reheated again at 1250°C for 30 minutes and hot rolled to a thickness of 3 mm at a finish rolling temperature (FRT) of 900°C (in the austenite phase region for all three steels). The temperatures at which steels A, B, and C transform from austenite to ferrite during cooling (Ar3) were measured by coefficient of thermal expansion to be 798°C, 805°C, and 725°C, respectively. Hot-rolled steel was subjected to a coil cooling simulation in a muffle furnace starting at 680°C and then cooled to room temperature. Next, the hot-rolled strip was annealed at 600°C for 96 hours in a muffle furnace under a protective atmosphere and air-cooled to room temperature. The strip was then pickled with HCl acid at 90°C to remove oxides and cold-rolled to a thickness of 1.5 mm using multiple passes.

[0072] Cold-rolled strips of steel A were subjected to continuous annealing at 675°C for 5 minutes, and cold-rolled strips of steels B and C were subjected to continuous annealing at 650°C for 5 minutes. Then, all steel strips were directly immersed in a zinc plating bath composed mainly of Zn alloy with 0.4 wt% Al (hot-dip galvanizing). The dimensions of the strips were 200 mm × 105 mm × 1.5 mm. The bath temperature was maintained at 465°C, with an immersion time of 5 seconds, and then the strips were cooled to room temperature at 5°C / second, similar to air cooling. These continuous annealing and hot-dip galvanizing simulations were performed using a hot dip annealing simulator. The atmosphere during soaking in the continuous annealing portion of the thermal cycle was set to NH5 gas with a dew point of -30°C and 5 vol% H2 gas. The atmosphere during heating (i.e., the initial part of continuous annealing) was varied at a fixed dew point of 20°C with air-fuel ratios (λ) of 0.98, 1.005, 1.01, and 1.02. It should be noted that the atmosphere was considered oxidizing when λ > 1, and reducing when λ < 1. A schematic diagram of the continuous annealing-hot galvanizing cycle, along with the subsequent hot press molding operation, is shown in Figure 1. Table 2 summarizes the oxygen content of the annealing atmosphere during the heating portion of continuous annealing for different λ values.

[0073] Next, the Zn-coated strips were hot-formed using a hot-forming press provided by Schuler SMG GmbH&Co.KG, employing the thermal cycles shown in Table 4. The thermal cycles are also schematically shown on the right side of Figure 1. Two types of forming tools were used: a flat tool for obtaining specimens for tensile, bending, contact resistance, corrosion, and microstructural testing, and a hat-top tool for obtaining omega-shaped profiles (Figure 2a) for microcrack inspection. Additional reheating time and temperature combinations were used for measuring contact resistance and corrosion (shown in Tables 10 and 11, respectively).

[0074] A 30mm x 200mm (rolling direction x transverse direction) zinc-plated strip was subjected to a Zn adhesion test used in the automotive industry. In this test, Betamate 1496V adhesive was applied to the center of both sides of the strip (length 150mm or more, thickness 4-5mm, width 10mm or more). The adhesive was then cured in an oven at 175°C for 30 minutes. The sample was then firmly clamped with the adhesive side facing outwards and bent at a moderate speed to a 90° angle with a bending radius of 1.1mm. The sample was then visually inspected and labeled with a code indicating the state of Zn delamination.

[0075] In accordance with the NEN10002 standard, the tensile test was performed at a quasi-static strain rate of 3 × 10⁻¹⁰. -4 s -1 The test was conducted using tensile test specimens with a gauge length of 50 mm and a width of 20 mm in the rolling direction. Three-point bending tests in accordance with the VDA238-100 standard were performed on 40 mm × 30 mm × 1.5 mm specimens in both the longitudinal and transverse directions, using a bending radius (= punch radius) of 0.4 mm. The bending angle was converted to a sheet thickness of 1.0 mm using the above formula.

[0076] The abbreviations and symbols used in the tables showing the results of tensile and bending tests are as follows: Rp = Yield strength, Rm = Maximum tensile strength, Ag = Uniform elongation, A 50 =Total elongation at a gauge length of 50 mm. BA = bending angle, L = longitudinal specimen with bending axis parallel to the rolling direction, T = transverse specimen with bending axis perpendicular to the rolling direction.

[0077] The amount of retained austenite was determined by X-ray diffraction (XRD) at a position where the sample thickness was 1 / 4. XRD patterns were recorded in the range of 45–165° (2θ) using a Panalytical Xpert PRO standard powder diffractometer (CoKα line). The phase ratio was quantitatively determined by Rietveld analysis using the Bruker Topas software package for Rietveld refinement. The martensite content was determined from the peak splitting at the ferrite diffraction position in the diffraction pattern.

[0078] For microcracks, a hot-formed omega-shaped profile was inspected. The dimensions of the omega profile and the microcrack inspection scheme are shown in Figure 2. A 1 cm wide section was cut from the Ω profile along the height. Using a 1000x magnification optical microscope, the specimen was inspected for microcracks in the cross-section of the coated sheet. For this purpose, a length of approximately 1 cm from the center of the profile towards the bottom was observed.

[0079] To obtain an index of the weldability of hot-formed materials, the contact resistance of hot-formed blanks of steels B and D was measured in accordance with ISO 18594 standard without sandblasting for a wide range of time and temperature combinations (shown in Table 10). The corrosion resistance of coated steels was also measured in accordance with sandblasting under the same reheating conditions. Corrosion tests of hot-formed steels B and D were carried out in accordance with VDA 621-415 standard. Each blank was treated with phosphoric acid, coated, and then scribbled. Wide and narrow scribes (1 mm and 0.3 mm wide, 100 mm long) were marked longitudinally on the sample, positioned parallel to each other. The distance between the two scribes was maintained at 30 mm, and the distance from the edge of the sample was maintained at 35 mm. An aqueous solution of 5 vol% NaCl + 10 g NaHCO3 (150 liters) was used as the corrosion medium. We monitored the formation of red rust (Zn oxide) on the scribes over several weeks, and the length (%) of the scribe covered with red rust was used as a measure of corrosion. For both corrosion resistance and contact resistance measurements, we also included unreheated 22MnB5 steel specimens for comparison.

[0080] Table 3 shows the results of the adhesion test of the Zn alloy coating. A "P" (=pass) indicates that the coating remained intact after the test, while an "F" (=fail) indicates that the coating delaminated during the test. When λ was 0.98, i.e., when oxygen was absent in the heated section during continuous annealing (see Table 2), the coating delaminated during the test for all three types of steel A, B, and C. On the other hand, when λ values ​​were 1.005 and 1.01 (corresponding to oxygen content of 800 and 1700 ppm by weight in the heated section), all three types of coated steel passed the coating adhesion test. However, when λ value was 1.02 (=oxygen content of 3700 ppm by weight in the heated section of continuous annealing), the coating delaminated during the test for all three types of steel. These results indicate that an optimal oxygen content exists during the heating of the steel strips in the continuous annealing process of the present invention in order to achieve good adhesion of the coating to the steel surface. In the absence of oxygen (λ=0.98), selective oxidation of Mn occurs on the steel surface and cannot be reduced back to metallic Mn. Therefore, the substrate surface is unsuitable for adhesion of Zn or Zn alloys during molten dipping. However, in the presence of excessively high oxygen levels (3700 ppm by weight) (λ=1.02), excessive iron oxides form a thick FeO layer on the steel surface. This surface is unsuitable for adhesion of Zn or Zn alloys. Furthermore, these FeO particles can be picked up by the rolls during the manufacturing process, potentially resulting in numerous surface defects. Table 5 shows the tensile properties of GI 22MnB5 steel grade (steel D) in its as-received state, as well as the tensile properties of the hot-dip galvanized steel, i.e., the steel before hot forming, and Table 6 shows the microstructure of the corresponding steel substrate. By using the transformation interval annealing temperature for soaking during continuous annealing, a high proportion of retained austenite, along with the desired amount of ferrite and a small amount of martensite, was obtained in all three types of steel of the present invention (Table 6).This was achieved by the enrichment of the transformation interval austenite by Mn and C during annealing, which improved the thermal stability of the austenite by lowering the Ms temperature. In contrast, the 22MnB5 steel grade, which has not been modified to the chemical composition of the present invention and has not been subjected to continuous annealing according to the purpose of austenite stabilization, has a ferrite-pearlite microstructure that does not contain retained austenite. The effect of the specific microstructures obtained in steels A, B, and C of the present invention is reflected in their mechanical properties (Table 5). These steels have much higher yield strength and tensile strength values, along with good total elongation, due to the enhanced strain hardening rate achieved from the TRIP effect of retained austenite. This benefit is also reflected in the higher Rm×A50 value (an indicator of the energy absorption capacity of steel) of the steels of the present invention.

[0081] Tables 7 and 8 show the mechanical properties after hot-press forming and the corresponding microstructural components of all steels, respectively. In the steels of the present invention under all reheating conditions, more than 30 volume% retained austenite was obtained in these microstructures. This is because Mn (and C) was distributed to the austenite during the transformation interval reheating. In steel B, with increasing reheating time, the retained austenite content increased for any given reheating temperature due to increased Mn distribution to the austenite. Generally, as the reheating temperature increases, the Mn distribution to the austenite decreases, resulting in a slight decrease in retained austenite content (this can also be shown by ThermoCalc calculations). In general, the retained austenite content of steels A, B, and C is similar before and after hot forming, or slightly higher after hot forming than before (Tables 6 and 8). Therefore, it may appear that there is little benefit from further Mn distribution during hot forming. However, this is not true, as is evident from the comparison of the corresponding total elongation, tensile strength, and product of total elongation and tensile strength performed below (Tables 5 and 7). In contrast to the retained austenite exceeding 30 vol% in the steel of the present invention, the conventional 22MnB5 steel grade produced a microstructure that was predominantly martensite (98.3 vol%) after hot forming. The ferrite content in the steel of the present invention is over 40 vol%, while the martensite content is less than 20 vol%.

[0082] As a result of the desired microstructure formed in the steel of the present invention, attractive mechanical properties were obtained (Table 7). Total elongation exceeding 20%, yield strength exceeding 800 MPa, and maximum tensile strength exceeding 950 MPa were achieved in the steel of the present invention. Steel with a high Mn content (steel C) also achieved higher maximum tensile strength and total elongation values ​​than steels with low Mn content (steels A and B) due to the higher amount of retained austenite. The energy absorption value (Rm × A50 value) of the steel of the present invention after hot forming is also very high. Conventional 22MnB5 steel achieved a tensile strength exceeding 1500 MPa, but its energy absorption capacity was much lower due to its low total elongation. The energy absorption capacity of the steel of the present invention under all reheating conditions is at least 2.5 times higher than that of 22MnB5 steel. The bending angle of the hot-formed steel of the present invention at a thickness of 1.0 mm is much larger than that of 22MnB5. Steels A, B, and C achieved a minimum bending angle of over 100°. As described above, these remarkable mechanical properties of the steel of the present invention are due to the high proportion of retained austenite phase in these microstructures, which results in high work hardening due to the TRIP effect. The additional Mn enrichment in the austenite during reheating is reflected in the fact that the hot-formed steel of the present invention has a higher energy absorption value than that of hot-dip galvanized steel.

[0083] Table 9 shows the results of the microcrack inspection. After hot forming of the steel of the present invention at a low temperature, a small number of short microcracks were present. However, GI 22MnB5 steel, which was hot formed at a high temperature using a conventional method, showed numerous long microcracks on its surface. The minimization of microcracks in the steel of the present invention is due to reheating and hot forming at a low temperature, which minimizes the diffusion and penetration of zinc into the steel grain boundaries and prevents metal embrittlement during hot forming. However, in the case of 22MnB5, the same benefits cannot be obtained because high temperatures are used.

[0084] Table 10 shows the results of contact resistance measurements. When the reheating temperature of the steel of the present invention (steel B) is up to 700°C with various soaking times up to 15 minutes, the contact resistance value is as low as that of plated (as-dipped) GI 22MnB5 (steel D) and much lower than that of GI 22MnB5 reheated at high temperatures (800-900°C). It should be noted that plated GI 22MnB5 is weldable, and therefore the low contact resistance value of the steel of the present invention after hot forming suggests that this steel is also weldable. However, reheating at 800°C increases the contact resistance value of steel B, which indicates oxidation of the Zn or Zn alloy coating. This affects the spot weldability of the hot-formed part, and therefore, from the viewpoint of weldability, the reheating temperature should be limited to 700°C or below.

[0085] A similar trend was observed in the corrosion results shown in Table 11. The formation of red rust gradually increased in steel B of the present invention at reheating temperatures up to 700°C, and then increased sharply at a reheating temperature of 800°C. Up to 700°C, the percentage of red rust was low, slightly higher than that of plated GI 22MnB5, indicating good corrosion resistance in the hot-formed product. This corrosion resistance is significantly higher than that of GI 22MnB5 (steel D) when hot-formed at 900°C. Therefore, these results suggest that the steel of the present invention exhibits high corrosion resistance due to its Zn or Zn alloy coating when the reheating temperature is limited to 700°C. Severe oxidation of the Zn-based coating at 800°C caused a sharp decline in corrosion resistance.

[0086] [Table 1]

[0087] [Table 2]

[0088] [Table 3]

[0089] Table 4

[0090] Table 5

[0091] Table 6

[0092] Table 7

[0093] Table 8

[0094] Table 9

[0095] Table 10

[0096] Table 11

Claims

1. 1. A method of hot press forming a steel article from zinc or zinc alloy coated steel strip, comprising the steps of: The steel strip has the following composition, in weight percent: C: 0.05-0.3; Mn: 3.0-12.0; Al: 0.04-3.0; Optionally, the following additional alloying elements: Si: less than 1.5 Cr: less than 2.0 V: less than 0.1 Nb: less than 0.1 Ti: less than 0.1 Mo: less than 0.5 One or more of the following: Inevitable impurities; and Fe: remainder having A method for producing zinc or zinc alloy coated steel strip, comprising the steps of: casting the molten steel into slabs; reheating the slab to a temperature above 1150°C and holding at that temperature for at least 60 minutes; hot rolling the steel into strip; coiling the hot rolled steel strip; pickling the hot rolled steel strip; Optionally, cold rolling the pickled hot rolled steel strip into a cold rolled steel strip, wherein In the case of cold rolling, the hot rolled strip after coiling and pickling is subjected to batch annealing at a temperature T for a time P; The temperature TB and the time PB are selected such that the microstructure in the steel after cooling to room temperature exhibits more than 60% by volume of ferrite; Successively annealing the strip according to an annealing thermal cycle, wherein The temperature of the steel strip increases in the heating section and then remains at a relatively stable level due to soaking in the soaking section; The soaking atmosphere is maintained at a temperature between TMIN and TMAX; TMIN is (TMAX-100°C), The continuous annealing is considered to end when the temperature of the steel strip is reduced in the annealing thermal cycle; TMAX is equal to or lower than the lowest temperature among (Ac3-100°C) and 700°C, The dew point of the soaking atmosphere is −40° C. to −10° C. The continuous annealing comprises pre-oxidizing the steel strip in a heating section in an annealing atmosphere having an oxygen content of 500 to 3000 ppm by volume; The soaking atmosphere is a reducing atmosphere, The duration of the continuous annealing, consisting of the heating section time and the soaking section time, is 150 seconds or more; hot dip galvanising a steel strip with zinc or a zinc alloy, The immersion time is 3 seconds or more. In the molten bath, the bath temperature is maintained at 420°C to 500°C; The zinc bath essentially comprises zinc and at least 0.1 wt.% Al, optionally up to 5 wt.% Al, and optionally up to 4 wt.% Mg, the balance of the bath comprising additional elements and unavoidable impurities, each of the additional elements being independently less than 0.3 wt.%; Including, A method of hot press forming a steel article comprising the steps of: Providing a blank cut from molten zinc or zinc alloy coated steel strip; reheating the blank to a blank temperature TRH of (Ac3-300°C) to 750°C; soaking the blank in TRH for more than 3 minutes but not more than 15 minutes; transferring the blank to a press within 30 seconds; forming the steel article in a press and then cooling the steel article; Removing steel articles from a press A method comprising:

2. The method of claim 1, wherein the Mn content is 6.0 wt.% or more.

3. 3. The method of claim 1 or 2, wherein the slab is reheated to a temperature above 1200°C and held at that temperature for at least 60 minutes.

4. A method according to any one of claims 1 to 3, wherein the slab is reheated to a constant temperature and held at that temperature for at least 120 minutes.

5. The method according to any one of claims 1 to 4, wherein TRH is from (Ac3-300°C) to 700°C.

6. A method according to any one of the preceding claims, in which the blank is transferred to the press within 10 to 15 seconds.

7. A hot-press formed molten zinc or zinc alloy coated steel article from steel strip, comprising: The hot press formed molten zinc or zinc alloy coated steel article comprises, in volume percent: Ferrite: 30% or more; Retained austenite: 20% or more; The remainder of the microstructure is martensite: 40% or less (including 0%) having a microstructure comprising The steel strip has the following composition, in weight percent: C: 0.05-0.3; Mn: 3.0-12.0; Al: 0.04-3.0; Optionally, the following additional alloying elements: Si: less than 1.5 Cr: less than 2.0 V: less than 0.1 Nb: less than 0.1 Ti: less than 0.1 Mo: less than 0.5 One or more of the following: Inevitable impurities; and Fe: remainder having A hot-press formed molten zinc or zinc alloy coated steel article, wherein the contact resistance of the hot-press formed molten zinc or zinc alloy coated steel article is 0.084 mΩ to 0.179 mΩ.

8. 8. The hot pressed formed molten zinc or zinc alloy coated steel article of claim 7, wherein the ferrite content of the microstructure is greater than or equal to 40%.

9. 9. A hot-press formed molten zinc or zinc alloy coated steel article according to claim 7 or 8, wherein the retained austenite content of the microstructure is 30% or more.

10. The following characteristics: Yield strength: 800 MPa or more; Tensile strength: 820 MPa or more; Total elongation: 10% or more; Minimum bending angle at a thickness of 1.0 mm: 80° or more The hot press formed molten zinc or zinc alloy coated steel article of any one of claims 7 to 9, having

11. The hot press formed molten zinc or zinc alloy coated steel article according to any one of claims 7 to 10, wherein the hot press formed molten zinc or zinc alloy coated steel article is composed of a steel substrate provided with a molten zinc coating layer, and the length of the microcracks in the steel substrate is 5 μm or less.